2022
DOI: 10.3390/jimaging8010007
|View full text |Cite
|
Sign up to set email alerts
|

Towards a First-Person Perspective Mixed Reality Guidance System for Needle Interventions

Abstract: While ultrasound (US) guidance has been used during central venous catheterization to reduce complications, including the puncturing of arteries, the rate of such problems remains non-negligible. To further reduce complication rates, mixed-reality systems have been proposed as part of the user interface for such procedures. We demonstrate the use of a surgical navigation system that renders a calibrated US image, and the needle and its trajectory, in a common frame of reference. We compare the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…Previous studies have already suggested MR-assisted vascular access procedures [16,31]. The study of Groves et al suggested improved accuracy results with the use of an HMD when compared with traditional sonography-guidance during central venous catheter placement in a phantom study [16]. To the best of our knowledge, the present study is the first to investigate the feasibility and the positional error of a MR-assisted approach for CFA access using an HMD combined with a commercially available navigation system.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Previous studies have already suggested MR-assisted vascular access procedures [16,31]. The study of Groves et al suggested improved accuracy results with the use of an HMD when compared with traditional sonography-guidance during central venous catheter placement in a phantom study [16]. To the best of our knowledge, the present study is the first to investigate the feasibility and the positional error of a MR-assisted approach for CFA access using an HMD combined with a commercially available navigation system.…”
Section: Discussionmentioning
confidence: 66%
“…Adequate visualization of the target vessel is key for a safe vascular access procedure. Previous studies have already suggested MR-assisted vascular access procedures [16,31]. The study of Groves et al suggested improved accuracy results with the use of an HMD when compared with traditional sonography-guidance during central venous catheter placement in a phantom study [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Operationssaal der Zukunft [2]. Verschiedene Anwendungsfälle von MR-Technologien wurden bereits für die Neurochirurgie [3], Orthopädie und Wirbelsäulenchirurgie [4], Thoraxchirurgie [5], Urologie [6], plastische Chirurgie [7], Viszeralchirurgie [8], interventionelle Radiologie [9], Anästhesie und Intensivmedizin [10,11,12,13,14,15], Gefäßchirurgie [16] und andere Fachdisziplinen beschrieben. Neben der intraoperativen Anwendung sind auch die Lehre und die Patientenaufklärung häufiger Gegenstand wissenschaftlicher Aktivität im Zusammenhang mit MR [17,18].…”
Section: Introductionunclassified